Bis(4-methoxychalcone 4-ethylthiosemicarbazonato-κ2 N 1,S)zinc(II): Crystal structure and Hirshfeld surface analysis - Tan, Ming Yueh; Crouse, Karen A.; Ravoof, Thahira Begum S. A.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (2018)
The title ZnII complex, [Zn(C19H20N3OS)2] {systematic name: bis[(N-ethyl-N0-{(Z)-[(2E)-3-(4-methoxyphenyl)-1-phenylprop-2-en-1-ylidene]amino}carbamimidoyl)sulfanido]zinc(II)}, features a tetrahedrally coordinated ZnII ion within an N2S2 donor set provided by two N,S-chelating thiosemicarbazone anions. The resulting five-membered Zn,C,N2,S chelate rings adopt different conformations, i.e. almost planar and an envelope with the Zn atom being the flap atom. The configuration about the imine bond within the chelate ring is Z but those about the exocyclic imine and ethylene bonds are E. In the crystal, supramolecular [100] chains mediated by thioamide-N—H...S(thione) hydrogen bonds and eight-membered thioamide {.....HNCS}2 synthons are observed. A range of interactions, including C—H...O, C—H...., C—H....(chelate ring) and .(methoxybenzene)—.(chelate ring) consolidate the packing. The Hirshfeld surface analysis performed on the title complex also indicates the influence of the interactions involving the chelate rings upon the packing along with the more conventional contacts.